2018
DOI: 10.3389/fimmu.2018.01745
|View full text |Cite
|
Sign up to set email alerts
|

Cell Signaling of Caenorhabditis elegans in Response to Enterotoxigenic Escherichia coli Infection and Lactobacillus zeae Protection

Abstract: Enterotoxigenic Escherichia coli (ETEC) infection causes the death of Caenorhabditis elegans, which can be prevented by certain Lactobacillus isolates. The host response of C. elegans to ETEC infection and its regulation by the isolates are, however, largely unclear. This study has revealed that, in agreement with the results of life-span assays, the expression of the genes encoding p38 mitogen-activated protein kinase (MAPK) pathway (nsy-1, sek-1, and pmk-1), insulin/insulin-like growth factor (DAF/IGF) pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 46 publications
4
43
1
Order By: Relevance
“…To determine the cell signaling of mutant cat-2 in response to the supplementation of dopamine in the life-span assay, the gene expression of major components in the p38-MAPK ( tir-1, nsy-1, sek-1 , and pmk-1 ) and IGF-1/DAF-16 ( age-1 and daf-16 ) pathways, previously identified antimicrobial peptides ( lys-7, spp-1, abf-2, clec-85, clec-60 , and abf-3 ), and other reported defense molecules ( sod-3, dbl-1 , and skn-1 ) was examined with the method described previously (Zhou et al, 2014 , 2018 ). The experiment was carried out in three parallels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the cell signaling of mutant cat-2 in response to the supplementation of dopamine in the life-span assay, the gene expression of major components in the p38-MAPK ( tir-1, nsy-1, sek-1 , and pmk-1 ) and IGF-1/DAF-16 ( age-1 and daf-16 ) pathways, previously identified antimicrobial peptides ( lys-7, spp-1, abf-2, clec-85, clec-60 , and abf-3 ), and other reported defense molecules ( sod-3, dbl-1 , and skn-1 ) was examined with the method described previously (Zhou et al, 2014 , 2018 ). The experiment was carried out in three parallels.…”
Section: Resultsmentioning
confidence: 99%
“…The life-span assays of C. elegans were performed as described with slight modifications (Zhou et al, 2018 ). Synchronized C. elegans was transferred to NGM agar with E. coli OP50 at 25°C until it reached the L4 stage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, other work in a nematode model of E . coli sepsis showed that only certain strains of Lactobacillus further increased MAPK activation during infection, resulting in better survival outcomes [ 43 ]. Further work is therefore needed to more fully understand the effect of Lactobacillus on this pathway as well as its downstream effect on pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the mechanisms involved in the action of Lcr35 ® against C. albicans, we studied the expression of seven C. elegans genes (Table 2) divided into three groups: daf-2 and daf-16 (insulin signaling pathway) involved in host longevity and antipathogenicity response, sek-1 and pmk-1 (p38 MAPK signaling pathway) which concern the immunity reaction as well as abf-2, cnc-4 and fipr-22/fipr-23 which encode antimicrobial proteins. The interest in targeting these genes has been demonstrated by various studies showing that the insulin and p38 MAPK pathways were involved in the pro-longevity properties of lactobacilli and bifidobacteria [12,[18][19][20], while the antimicrobial genes were involved in the anti-Candida effect [21]. In comparison with the E. coli OP50 control condition, we noted that Lcr35 ® induced an overexpression of daf-16 (p = 0.0004) and had no effect on daf-2 (p = 0.9459), while C. albicans tended to induce an up regulation of daf-2 (p = 0.0922) and a down-regulation of daf-16 (p = 0.4959).…”
Section: Modulation Of C Elegans Genes Expression Induced By Lcr35 ®mentioning
confidence: 99%